(untitled) (Journal of Atomic and Molecular Sciences, 2019)
We theoretically study the photofragmentation reaction of the hydrogen molecular ion H^+_2 by a single intense ultrashort laser pulse. Simulation results obtained from numerical solutions of time-dependent Schrödinger equations show that quantum interference patterns are constructed in the photofragment spectra and the induced angular distributions of photofragments are sensitive to the wavelength of the laser pulse. These phenomena are successfully explained by using the concept of the light-induced conical intersection.